Quantifying Turning Tasks With Wearable Sensors: A Reliability Assessment. - Weston, Angela R; Antonellis, Prokopios; Fino, Peter C; Hoppes, Carrie W; Lester, Mark E; Weightman, Margaret M; Dibble, Leland E; King, Laurie A (PTJ: Physical Therapy & Rehabilitation Journal, 2024)
Objective The aim of this study was to establish the test–retest reliability of metrics obtained from wearable inertial sensors that reflect turning performance during tasks designed to imitate various turns in daily activity. Methods Seventy-one adults who were healthy completed 3 turning tasks: a 1-minute walk along a 6-m walkway, a modified Illinois Agility Test (mIAT), and a complex turning course (CTC). Peak axial turning and rotational velocity (yaw angular velocity) were extracted from wearable inertial sensors on the head, trunk, and lumbar spine. Intraclass correlation coefficients (ICCs) were established to assess the test–retest reliability of average peak turning speed for each task. Lap time was collected for reliability analysis as well. Results Turning speed across all tasks demonstrated good to excellent reliability, with the highest reliability noted for the CTC (45-degree turns: ICC = 0.73–0.81; 90-degree turns: ICC = 0.71–0.83; and 135-degree turns: ICC = 0.72–0.80). The reliability of turning speed during 180-degree turns from the 1-minute walk was consistent across all body segments (ICC = 0.74–0.76). mIAT reliability ranged from fair to excellent (end turns: ICC = 0.52–0.72; mid turns: ICC = 0.50–0.56; and slalom turns: ICC = 0.66–0.84). The CTC average lap time demonstrated good test–retest reliability (ICC = 0.69), and the mIAT average lap time test–retest reliability was excellent (ICC = 0.91). Conclusion Turning speed measured by inertial sensors is a reliable outcome across a variety of ecologically valid turning tasks that can be easily tested in a clinical environment. Impact Turning performance is a reliable and important measure that should be included in clinical assessments and clinical trials.